Penerapan Metode Promethee Dalam Sistem Pendukung Keputusan Pemilihan Kampus Terbaik Di Kabupaten Asahan - Finki Maylani; Revina Salsabila; Siti Nuraida Mangunsong; Rani Kharisma Azzahra (J-Com (Journal of Computer), 2026)
Abstract: The development of information technology has brought significant transformation in the field of education, particularly in academic decision-making. This study aims to develop a Decision Support System (DSS) based on the PROMETHEE method (Preference Ranking Organization Method for Enrichment Evaluation) to assist prospective students in objectively and systematically selecting the best university in Asahan Regency. The main issue addressed is the lack of integrated information regarding the strengths of each educational institution, as well as the absence of a recommendation system that considers various important criteria such as accreditation, facilities, tuition fees, achievements, and study programs. This research uses a quantitative approach with data collection techniques including observation, interviews, questionnaires, and documentation. The implementation results of the PROMETHEE method show that Royal University achieved the highest ranking, followed by Asahan University and STIKES As Syifa Kisaran. This method has proven effective in producing rational and transparent campus rankings based on multi-criteria preferences. The findings are expected to serve as a reference for prospective students and educational institutions in improving the quality and competitiveness of higher education in the Asahan region. Keywords: decision support system promethea; campus selection; multi-criteria; asahan. Abstrak: Perkembangan teknologi informasi telah membawa transformasi signifikan dalam dunia pendidikan, khususnya dalam pengambilan keputusan akademik. Penelitian ini bertujuan untuk membangun sistem pendukung keputusan (SPK) berbasis metode PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) guna membantu calon mahasiswa dalam memilih kampus terbaik di Kabupaten Asahan secara objektif dan terstruktur. Permasalahan yang diangkat adalah kurangnya informasi terintegrasi mengenai keunggulan masing-masing institusi pendidikan serta belum tersedianya sistem rekomendasi yang mempertimbangkan berbagai kriteria penting seperti akreditasi, fasilitas, biaya pendidikan, prestasi, dan program studi. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik pengumpulan data melalui observasi, wawancara, kuesioner, dan dokumentasi. Hasil implementasi metode PROMETHEE menunjukkan bahwa Universitas Royal memperoleh peringkat tertinggi diikuti oleh Universitas Asahan dan STIKES As Syifa Kisaran. Metode ini terbukti mampu menghasilkan peringkat kampus secara rasional dan transparan berdasarkan preferensi multikriteria. Temuan ini diharapkan dapat menjadi acuan bagi calon mahasiswa dan pihak institusi dalam meningkatkan kualitas dan daya saing perguruan tinggi di wilayah Asahan. Kata kunci: sistem pendukung keputusa; promethee; pemilihan kampus; multi kriteria; asahan